PENGUATAN INTEGRASI NASIONAL DAN IMPLIKASINYA TERHADAP KETAHANAN SOSIAL BUDAYA (Studi Pada Masyarakat Kota Surakarta Provinsi Jawa Tengah ) - , WIJIANTO, Prof. Dr. Kodiran, MA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Surakarta city is a heterogeneous and dynamic city. It is also known as a city of education, culture, and tourism which becomes the political and economic barometer. The objectives of this research are: (1) to describe the strengthening of national integration of the people of Surakarta city